Role of fluorescence study in diagnosis of reccurent skin cancer (case report) - E. V. Filonenko; V. V. Sokolov (Biomedical Photonics, 2013)
The case of diagnosis of recurrent skin cancer using fluorescence methods is reported. The patient who underwent multiple courses of treatment (surgical resection, cryotherapy and laser ablation) for multifocal basal cell carcinoma of head. trunk and extremities. The patient represented with multiple whitish scars in the region of surgery, cryotherapy and laser ablation (one of them was in the region of external ear) and with multiple foci of hyperemia and skin peeling. The patient underwent fluorescence diagnosis according to developed regimen: alasens was given per os at a dose of 30 mg/kg body weight 4 h before study. In the white light there were no features of recurrent tumor in scar areas. During fluorescence examination there was bright red fluorescence in the area of ear scar, which was intact visually, with no additional fluorescence foci in regions of surgical resection, cryotherapy and laser ablation and other regions. According to cytological study of shave biopsy from fluorescecnse area of ear scar the recurrence of basal cell skin carcinoma was diagnosed.